PI3K/AKT pathway as a key link modulates the multidrug resistance of cancers - Liu, Rui; Chen, Youwen; Liu, Guangzhi; Li, Chenxi; Song, Yurong; Cao, Zhiwen; Li, Wen; Hu, Jinghong; Lu, Cheng; Liu, Yuanyan (Cell death & disease, 2020)
Multidrug resistance (MDR) is the dominant challenge in the failure of chemotherapy in cancers. Phosphatidylinositol 3-kinase (PI3K) is a lipid kinase that spreads intracellular signal cascades and regulates a variety of cellular processes. PI3Ks are considered significant causes of chemoresistance in cancer therapy. Protein kinase B (AKT) is also a significant downstream effecter of PI3K signaling, and it modulates several pathways, including inhibition of apoptosis, stimulation of cell growth, and modulation of cellular metabolism. This review highlights the aberrant activation of PI3K/AKT as a key link that modulates MDR. We summarize the regulation of numerous major targets correlated with the PI3K/AKT pathway, which is further related to MDR, including the expression of apoptosis-related protein, ABC transport and glycogen synthase kinase-3 beta (GSK-3β), synergism with nuclear factor kappa beta (NF-κB) and mammalian target of rapamycin (mTOR), and the regulation of glycolysis.